Assessment of surface corrosion on carbon steel plates using a differential fluxgate probe - Mohd Mawardi, Saari; Mohd Aufa Hadi Putera, Zaini; Ummi Sabihah, Mohd Yusdi; Nurul A'in, Nadzri; Mohd Herwan, Sulaiman; Kiwa, Toshihiko (Wydawnictwo SIGMA-NOT, 2023)
In this work, magnetic responses from artificial corrosion defects were investigated using a differential fluxgate probe. Different rates of corrosion defects were prepared based on the electrolytic corrosion process on the surface of a carbon steel plate by manipulating the corrosion period. Then, the differential fluxgate probe, consisting of two miniature fluxgates arranged in a planar configuration and a circular excitation coil, was used to measure the real and imaginary components of magnetic responses from the corrosion defects in the range of 5 to 510 Hz. The real differential magnetic response from the probe showed that the magnetic signal change was proportionally increased with the corrosion period, revealing the increased depth of the corroded region with the electrolytic corrosion period. The magnetic response induced by an excitation field from 10 to 110 Hz could be utilized to enable a sensitive depth estimation of a corrosion defect on high-permeability steel at a sub-millimeter resolution.